2005
DOI: 10.1038/nsmb949
|View full text |Cite
|
Sign up to set email alerts
|

TFIIH XPB mutants suggest a unified bacterial-like mechanism for promoter opening but not escape

Abstract: DNA helicases open the duplex during DNA replication, repair and transcription. However, RNA polymerase II is the only member of its family with this requirement; RNA polymerases I and III and bacterial RNA polymerases open DNA without a helicase. In this report, characterization of XPB mutants indicates that its helicase activity is not used for RNA polymerase II promoter opening, which is instead driven by its ATPase activity. The mutants have parallels in sigma(54) bacterial transcription and this suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 37 publications
1
75
0
1
Order By: Relevance
“…For 54 , ATP-dependent activator proteins are hypothesized to remodel the downstream jaw by means of interactions with the NTD of 54 . Similarly, ATP hydrolysis by the transcription factor TFIIH has been proposed to drive large-scale protein rearrangements in the pol II preinitiation complex to allow DNA melting (30). This hypothesis contrasts with the generally accepted model that invokes ATP-driven conformational changes in the helicase domains of TFIIH to open DNA (4).…”
Section: Comparison Of the Extent Of Dna Opening In Rpo With I1 Usingmentioning
confidence: 99%
See 1 more Smart Citation
“…For 54 , ATP-dependent activator proteins are hypothesized to remodel the downstream jaw by means of interactions with the NTD of 54 . Similarly, ATP hydrolysis by the transcription factor TFIIH has been proposed to drive large-scale protein rearrangements in the pol II preinitiation complex to allow DNA melting (30). This hypothesis contrasts with the generally accepted model that invokes ATP-driven conformational changes in the helicase domains of TFIIH to open DNA (4).…”
Section: Comparison Of the Extent Of Dna Opening In Rpo With I1 Usingmentioning
confidence: 99%
“…At 17°C, where the equilibrium constant K 1 is a maximum and conversion of I 1 to I 2 is relatively slow, we previously found that the fraction of promoter DNA in I 1 complexes ( I1 ) at 15 sec after mixing P R promoter with 70 nM (excess) RNAP was 0.55 (6). To increase the fraction of I 1 in the time interval (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) (38) where the only complex predicted to be populated is I 1 (9). Because the signal:noise ratio in these 0°C experiments was marginal, and to avoid the possibility of populating off-pathway complexes at 0°C (39), we identified solution conditions where I 1 is Ͼ70% of promoter DNA (see above) at early times in the time course of RP o formation, and footprinted as follows.…”
Section: Determination Of Fractions Of Promoter Dna In I1 and Rpo Commentioning
confidence: 99%
“…Biochemical and genetic studies have shown that both XPB and XPD ATPase activities are needed to open up DNA around a damaged site (18,19). Recent data showed that only XPB ATPase activity of is required for opening and remodeling of DNA in NER and transcription, and its helicase is devoted to promoter escape in transcription (20,21). XPD helicase activity, on the other hand, plays a minor role in transcription but is necessary for NER (19,22).…”
mentioning
confidence: 99%
“…In both cases, passing from the closed to the open RNAP promoter complex requires activator proteins that hydrolyze nucleoside triphosphate to drive open RNAP promoter complex formation (3). The 54 -RNAP binds to specific promoter sites centered on positions Ϫ24 and Ϫ12 relative to the transcription start site and remains in a transcriptionally silent conformation.…”
mentioning
confidence: 99%